(3TQM CTcGd GdJCSjSs - (3RGOg GdQheis; (3GdSeQbfOj , TeS GdOjf eMeO Hf GTQa GdMSjfj GdSeQbfOj,J (B690 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb cd TF HbOQg hHYO aEf GdgfOSI eY eJCfI eSGFdgG Ef GdeNJUQ GdeSei HCTcGd GdJCSjS fYe GdYhf dWGdHjgG s
(3BNQgG (B:s
(3jchf LejY GdPi gh SWM Ch GdPi gh GdNW eY GdRjGOI ai h d CYfi O H hPdc eG CQOfGg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B39 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B63s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B105s
Keywords: (3GdQjGVjGJs